1970s: Turn of an Era in the History of Science?1. (8th January 2018) - Heymann, Matthias
Abstract: The decade of the 1970s has recently received a lot of attention in historical research. It is commonly described as 'a turn of an era', a time of deep economic, social and cultural transformation. Where do the sciences feature in this picture of the 1970s? This spotlight sheds light on an understudied period of time in the history of science.